Analisis Perilaku Konsumen terhadap Saluran Digital dan Fisik terhadap Strategi Omnichannel pada Multiple Case Study UMKM Bali - Tesar Librian Priyo Susilo; I Gusti Ngurah Agung Aditya Pramana (Lembaga Pengembangan Kinerja Dosen, 2026)
The development of digital technology and internet penetration are driving changes in consumer behavior and demanding that MSMEs not only adapt but also understand the operational motives and marketing channel integration strategies to face competition in the digital era. This study aims to examine the operational motives and technical adaptation processes of Micro, Small, and Medium Enterprises (MSMEs) in Bali in integrating online and offline marketing channels through an omnichannel strategy to respond to intense market competition in the digital era. This descriptive qualitative research uses a multiple case study approach in three different MSME sectors: goods maintenance services, creative services, and fashion retail. Data collection was conducted through direct observation, in-depth interviews, and a review of digital activities, then analyzed through single-case and cross-case stages. The results show that MSMEs optimize digital channels as instruments to expand reach and trigger consumer emotional engagement through a visual storytelling approach, while physical stores are crucially maintained as points of sensory validation. Functional integration has been proven to accommodate the shift in consumer behavior towards a hybrid decision-making pattern. In this pattern, consumers conduct information searches and initial evaluations online, but tend to shift to offline interactions to validate quality and finalize transactions to minimize purchase risk. In conclusion, cross-channel operational synergy has proven essential in boosting the competitive advantage of MSMEs.